Development of an Artificial Intelligence-Based Visual Arts Teaching Module for Elementary School Students within the Context of Palembang Culture - Febrian Syehan Armanda; Siti Dewi Maharani; Erna Retna Safitri (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study aimed to analyze the need for developing an Artificial Intelligence (AI)-based art learning module integrated with Palembang local culture for elementary school students. The study was motivated by the limited availability of interactive learning media and local culture-based modules, which contributed to low student engagement and understanding in art education. The research employed a descriptive qualitative approach using the Rowntree development model, which includes needs analysis, design, and preliminary evaluation stages. The study was conducted at SD Yayasan Harapan Masa Depan Cerah, Banyuasin, South Sumatra, involving elementary school teachers and third-grade students. Data were collected through observations, interviews, and questionnaires covering pedagogical, technical, cognitive, aesthetic, socio-cultural, and evaluative aspects related to students, teachers, and learning media. The findings revealed that all aspects were categorized as high to very high. Aesthetic and cognitive aspects emerged as the dominant needs among students and learning media, while pedagogical and technical aspects were dominant among teachers. These findings highlight the importance of developing AI-based modules that are visual, interactive, contextual, and adaptive to Palembang local culture. The integration of AI and ethnopedagogical approaches is considered capable of supporting creativity, cultural literacy, and student engagement in elementary school art learning.